Pengaruh Pemberian Air dan Beberapa Jenis Pupuk Organik terhadap Pertumbuhan dan Produksi Tanaman Kedelai (Glycine max L. Merril) - Iswanto Iswanto; Nurhayati Nurhayati; Rahmad Setia Budi (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
This research was conducted in the greenhouse of the Faculty of Agriculture, Islamic University of North Sumatra, Gedung Johor Village, Medan Johor District, Medan City, North Sumatra Province with an altitude of 25 meters above sea level and flat topography. This study was carried out from February to April 2021. This study aims to determine the growth and production of the comparison of water and organic fertilizer application of rice husk, roasted rice husk, straw, market vegetable waste on soybeans (Glycine max). This study used a factorial randomized block design (RBD) with two factors, namely:The water supply factor consists of 3 stages (volume), namely: P1 = watering: 1 day 1 watering (1000 ml of water), P2 = watering: 3 days 1 watering (1000 ml of water), P3 = watering: 6 days 1 time watering (1000 ml of water), Organic Fertilizer Provision Factor Consists of 4 Stages (Dosage) Namely: O1 = Rice Husk (20 tons/ha) = 100 g/polybag, O2 = Roasted rice husk(20ton/ha) )= 100g/polybag, O3 = Straw (20 tons/ha) = 100 g/polybag O4 = Organic fertilizer market vegetable waste (20 tons/ha) = 100 g/polybag, height plants, leaf area, number of branches, root length, flowerage, root nodules, root volume, crown base weight, canopy dry weight, production weight. The results can be seen that the effect of giving water has a very significant effect on the average root length, root nodules, volume on the growth and production of soybean plants and the effect of giving organic fertilizers has a very significant effect on the average root length, volume on growth and production of soybean plants.